Обнаружение наночастиц железа в водных растворах с помощью микроволнового сенсора - Одабашьян, Л.; Маргарян, Н.; Оганян, Г.; Манвелян, М.; Амбарян, Д.; Абраамян, Т.; Хачатрян, Р.; Бабаджанян, А. (Հայաստանի ԳԱԱ)
The aqueous solution with iron nanoparticles investigated by a microwave stripline sensor based on the optimized double quadratic-shape design. Due to real-time near-field electromagnetic interaction between microwaves and sample S11 reflection coefficient of the sensor was changed depending on iron nanoparticles concentration in the aqueous solution at resonant frequency. In this work we examined the iron nanoparticles concentration in the 0–20 μg/l concentration range at an operating frequency at about 1.7 GHz. The measured minimum detectable signal was 0.035 dB/(μg/l) or and 0.25 MHz/(μg/l) and the measured minimum detectable concentration was 1.4 μg/l and 0.2 μg/l, respectively. The microwave response of sensor systems can be explained by the additional structural changes of water clusters due to the metal nanoparticles ablation. This implemented method has approachable development process and the accuracy of measurement is high, thus it can be applied as a physiochemical sensor for non-invasive monitoring of metal nanoparticles in complex liquids.
Keywords: Nanotechnology; Physics of Fluids